Współczesne rytuały wchodzenia w dorosłość - osiemnaste urodziny i egzamin dojrzałości w percepcji młodych Lubuszan = Contemporary rites of passage into adulthood - the 18th birthday and the "matura" examination from the perspective of young people in Lubuskie Province - Trzop, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The word "rite" once inextricably linked to the sacred, does not refer only to the past. Ritual behavior is still with us today. It is not only associated with festive occasions or religious practices, but also with the passage from one stage of life to another, or with the assumption of new social roles. The way these rituals are celebrated, which has changed over the centuries, is itself a research field.
Keywords: rite; entering adulthood; adulthood markers; "matura" examination; coming of age; rytuały; wchodzenie w dorosłość; markery dorosłości; egzamin maturalny; pełnoletność